NATURAL PROMASTIGOTE INFECTION OF SERGENTOMYJA SINTONI ITS SEASONAL VARIATION AND RESERVOIR HOST IN TURKEMEN SAHAPA IRAN - M.A. Seyedi Rashti; Agh-Atabay; M. Mohebali (Tehran University of Medical Sciences, 1994)
A six month Survey (May-October1994) was conducted, to study natural promastigote infection of S.sintoni, its seasonal variation and reservoir host, in Turkemen Sahra, Iran. Sixty out of 403 S.sintoni dissected were found infected with promastigotes. This investigation showed that the peak of promastigote infection occurs in July (18.4%) and August (28.5%). Five lizards including one Cyrtoopodion caspius (Eichwald, 1831), two Trapelus agilis (Oliver 1804) and two Eremias velox (Pallas 1771) were captured, among them C.caspius was infected. Promastigotes were isolated from S.santoni and C.caspius and both isolates were identified as L.(Saurolejshmaini) gymnodactyli by isoenzyme characterization. This is the first report of isolation and characterization of this parasite from the vector and vertebrate host of lizard leishmaniasis in Iran.